2021
DOI: 10.1017/s0305000920000732
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and the acquisition of gender

Abstract: Children's differing learning trajectories cross-linguistically have been at the forefront of gender acquisition research, often with conflicting results and conclusions. As a result, the source of children's different learning behaviors in gender acquisition has been unclear. I argue that children's gender acquisition is driven by the search for productive patterns. First, I provide corpus studies where the predictions of a learning model (Yang, 2016) are formulated. Second, I report the results of an elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…The linear regression and step function analyses indicated that the learning was categorical, rather than gradient. That is, infants responded quantally, as did older children in Bjornsdottir (2021). The lack of productivity gradience in infants is consistent with the regularization performance (rather than probability matching) shown in 5-to 7-year-old children (Hudson Newport, 2005, 2009;Austin et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The linear regression and step function analyses indicated that the learning was categorical, rather than gradient. That is, infants responded quantally, as did older children in Bjornsdottir (2021). The lack of productivity gradience in infants is consistent with the regularization performance (rather than probability matching) shown in 5-to 7-year-old children (Hudson Newport, 2005, 2009;Austin et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
“…Recent corpus studies showed support for TP-predicted (un)productiveness and quantalness of morphosyntactic patterns in adult speech (Pearl and Sprouse, 2021;van Tuijl and Coopmans, 2021;Henke, 2022) and in historical texts (Kodner, 2023). Furthermore, experiments on English-speaking 5-8-year-olds' and Icelandicspeaking 2.5-to-6-year-olds' production of morphological patterns (Schuler et al, 2016;Bjornsdottir, 2021) and on Russian-speaking 4-6-year-olds' ordinal acquisition (de Vries et al, 2021) provided evidence for this theory. Yang (2016)'s analysis of the CHILDES corpora showed that children's productivity and overgeneralization of English verb morphology was fully predictable by TP; notably, TP also correctly predicted the finding that children almost never produced irregularizations such as "wipe-wope" (only 0.02% such analogy errors in Xu and Pinker, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…This learning model has been shown to correctly predict generalizations in corpus data from a wide range of different languages (e.g. Fernández-Dobao and Herschensohn 2019; Merkuur et al 2020;Garcia 2019;Björnsdóttir, 2021) and childhood behavior in certain experimental settings (Schuler et al 2016). We expect our findings to be compatible with other generative learning models.…”
Section: Methodmentioning
confidence: 99%
“…Following these case studies, Pophristic and Schuler (2021) employ the TP to draw predictions about the productivity of noun suffixes in Serbian, although they do not actually test these predictions with child language data. Björnsdóttir (2021) applies the TP to generate and test predictions about the acquisition of noun inflection in Icelandic, using corpus and experimental data to argue that children follow patterns corresponding to productive and unproductive rules predicted by the TP.…”
Section: Theoretical Backgroundmentioning
confidence: 99%